THE LEGAL OVERVIEW OF MEDIATION IN THE TREATMENT OF HARASSMENT IN THE WORKPLACE (MOBBING) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Harassment in the workplace (Mobbing) is consider a frequent phenomenon present in every sector (publicor private) which, due to the consequences it leaves behind for the victims, is considered very harmful andsometimes very hard to treat. It represent a number of different activities taken towards the employee/workerthat unfortunately affects negatively his/her well-being. To consider these activities as harassment activities,they must be characterized by repetition for a longer period of time (at least 6 months systematically) whichare presented as hostile, unethical, verbal or nonverbal behavior that affects an individual and sometimes agroup, with the final aim of termination of the employment contract done voluntary through resignationfrom the work. Because of the multidimensional negative effects, that mobbing can leave such as in thephysical and psychological health of the worker, also on his/her family life and social relationships andperformances at work, it must be treated very quickly and in the most efficient way. As a perfect methodthat can be identified with these two characteristics, is Mediation. It’s considered suitable for solving thesekind of “issues in the workplace” because of the high involvement of the emotions and psychological effectsthese emotions can cause to the worker, and because of the faster solution provided by this alternativemethod in comparison with other judicial or non-judicial methods. The main purpose of this paper will toachieve an extensive legal analysis of the laws that regulate this phenomenon in our society and of the lawthat provides its fast solution and treatment i.e. Law on mediation.
Keywords: Mobbing, Harassment in workplace in RNM, Mediation, ADR methods